Mexico : Arrangement Under the Flexible Credit Line and Cancellation of the Current Arrangement. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses Mexico's Request for Arrangement Under the Flexible Credit Line (FCL) and Cancellation of the Current Arrangement. Mexico's macroeconomic policies and policy frameworks remain very strong. Real GDP growth is projected to accelerate to 3.5 percent in 2015. The authorities are requesting a new FCL arrangement for two years at the same level of access. In their view, the risk of a rapid rebalancing of investor portfolios away from emerging markets remains elevated. The IMF staff considers the proposed access level of SDR 47.292 billion to be appropriate. Uncertainties surrounding the global outlook, including risks related to the tightening of monetary policy in the United States, remain high.